2018
DOI: 10.1089/neu.2017.5299
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory of Functional Independent Measurements during First Five Years after Moderate and Severe Traumatic Brain Injury

Abstract: A better understanding of long-term functional recovery process for patients with traumatic brain injury (TBI) facilitates effective rehabilitations. The aim of this study was to classify and characterize patients with moderate-to-severe TBI based on their functional trajectories up to 5 years post-injury. The study included 121 patients with moderate-to-severe TBIs (International Classification of Diseases, Tenth Revision [ICD-10], S06.0-S06.9), 16-55 years of age, and admitted at Trauma Referral Hospital wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…The present study analyzed data from the surviving population with complete GOSE data at the 1-year follow-up ( n = 97), with an attrition rate of 21% from the 1–10-year follow-up. A series of papers on functional outcome and health-related quality of life have previously been published based upon the same longitudinal cohort ( 15 , 31 , 42 51 ), please see Howe et al ( 43 ) for a detailed flowchart of the follow-up process up to 10 years after injury.…”
Section: Methodsmentioning
confidence: 99%
“…The present study analyzed data from the surviving population with complete GOSE data at the 1-year follow-up ( n = 97), with an attrition rate of 21% from the 1–10-year follow-up. A series of papers on functional outcome and health-related quality of life have previously been published based upon the same longitudinal cohort ( 15 , 31 , 42 51 ), please see Howe et al ( 43 ) for a detailed flowchart of the follow-up process up to 10 years after injury.…”
Section: Methodsmentioning
confidence: 99%
“…Improvements continued for up to 5 years after injury. 17 Wabl et al also found delayed functional recovery common beyond 6-12 months in a neurointensive care unit, including patients with severe stroke and TBI. 11 Andelic et al found that recovery may occur at intervals even further from injury.…”
Section: Discussionmentioning
confidence: 96%
“…[9][10][11][12][13][14][15] For those patients that do survive the initial hospitalization, a proportion will continue to improve for up to 10 years postdischarge. [16][17][18][19] While controversy exists with respect to which factors are associated with improved functional outcomes after discharge, age and severity of injury are common elements in many studies. 12,14,16,17,19 A lack of consistent functional outcome data can lead to a conundrum for the care team concerning the appropriate level of support for the patient with a severe TBI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study is an extension of an existing longitudinal TBI research project (3,41,42). It is the first study to report on self-reported competency over a 10-year trajectory and investigate predictive demographic and injury-related factors for self-reported functional outcomes.…”
Section: Strengths and Limitationsmentioning
confidence: 99%